네트워크 및 정보 알고리즘 기반 심리학 분석 - 김유리(Yuree Kim); 안새미(Sammy An); 김학용(Hak Yong Kim) (한국콘텐츠학회 논문지, 15(7), 2015)
In the period of spirit revolution, psychology for studying human mind is one of the important fields with humanities. To analyze for correct understanding of popularization of psychology, for future psychology research trends, and for correlation of the psychological sub-fields as a linker between natural and social sciences, we employed network technology and informatic algorithm to be more objective. By elucidating core key words from bipartate network that consists of terms and their explaining words in psychological glossary, we provide psychological contents for understanding psychology. As analyzing lots articles obtained from Korean Journal of Psychology and Annual Review of Psychology, it was possible to observe research trends of the psychological sub-fields. To analyze the correlation among sub-fields of the psychology, we extracted and compared title words of the articles that had published on Psychological Review over the past fifteen years. We also employed a pair-wise comparison matrix algorithm and then elucidated the correlation among sub-fields of the psychology. By this research, we expect to contribute not only providing information about popularization of psychology, analysis of research trends, and correlation among sub-fields of the psychology, but also providing convergent contents that conflate the psychology and the informatic technologies. 21세기 정신혁명 시대에 인문학과 더불어 중요성이 대두되는 분야는 인간의 마음을 다루는 심리학이다. 본 연구에서는 심리학의 대중화에 따른 올바른 이해, 심리학의 연구 동향, 자연과학과 사회과학을 연결고리로써의 심리학 세부 분야 사이의 상관관계를 분석하고자 네트워크 기술과 정보기술 알고리즘을 도입하여 객관적인 결과를 도출하고자 하였다. 심리학개론에 등장하는 용어 및 그 용어를 설명하는 단어로 구성된 bipartate 네트워크를 구축하고 핵심용어를 추출하여 제공함으로써 심리학 이해를 위한 콘텐츠 정보를 제공하고자 하였다. 한국심리학회지 및 Annual Review of Psychology에 실린 논문수를 기반으로 지금까지의 심리학 세부 분야의 발전 동향을 제공하였다. 최근 15년 동안 Psychological Review에 실린 논문 제목을 기반으로 정보 알고리즘을 사용하여 심리학 세부분야 간의 상관관계를 분석하였다. 이는 자연과학과 사회과학의 연결고리로써 심리학 세부 분야의 위상을 이해하는데 도움을 줄 것이다. 결론적으로 본 연구결과는 심리학의 대중화, 동향분석, 심리학 세부 분야의 위상에 관한 정보를 제공할 뿐만 아니라, 심리학과 정보과학 기술을 접맥시켜 심리학 기반 융합콘텐츠에 대한 정보를 제공하는데 기여할 수 있을 것으로 기대한다.